Hematology, serum chemistry and physiological characteristics of captive south pudu pudu pudu - Montes, Gustavo; Vásquez, Andrés; Flores, Estefanía; Cattaneo, Gino; Acuña, Mariana; Cattan, Pedro (Avances en Ciencias Veterinarias, 2004)
-